KONSEP PEMIKIRAN PENDIDIKAN MENURUT SYAIKH AZ-ZARNUJI DALAM KITAB TA'LIMUL MUTA’ALIM - Muhammad Ibnu Faruq Fauzi (Al-Rabwah, 2022)
Az-Zarnuji's thoughts in the book of Ta'limul Muta'allim contain adab-adab in education about student learning morals and teacher character. The focus of this research is How does Az-Zarnuji think about education in the book of  Ta'limul Muta'allim? The research method is qualitative research in the form of library research (library research) In order to get valid research results, it is necessary to select sources, both primary data sources and secondary data sources. The primary data source of this research is the book "Ta'limul Muta'alim" by Imam Az-Zarnuji, and the secondary source is the translation of Ta'limul Muta'alim, as well as other relevant and relevant books. The results of the research findings of this study show that the Educational Thought of the Book of Ta'limul Muta'alim according to Az-Zarnuji is needed in the world of education Characteristics of his thinking can be classified in practice patterns that stick to the Qur'an and hadith. Another tendency in his thinking is to present ethical values that breathe Sufistics. The moral education that he emphasized can be clarified into three, namely: First, morals to God, teachers, and disciples in the process of teaching and learning are intended only for God, Secondly, morals to fellow human beings, especially between students and teachers but at least to fellow friends must respect and respect each other. Third, morals to science itself, that science is light to us and the highest position is a knowledgeable person.